The Erosion of Pancasila Values ​​in Social Life Along with the Development of the Era and Technology - Suci Permata Nadia; Putri Yulinda Nasution; M. Rifqi Fauzan; Zaky Hardian (JUSTICES: Journal of Law, 2025)
The values ​​of Pancasila are the basis of the life of society, nation, and state. The five principles of Pancasila are interrelated and form a complete unity. Each principle cannot be applied separately, because they are interrelated with each other. This article discusses the fading of Pancasila values ​​in social life along with the development of the era and technology and also raises awareness of the importance of Pancasila values ​​in social life along with the development of the era and technology. In this study I used the library research method. The research is today, such as the first principle which emphasizes the values ​​of divinity and religiosity, the second principle which emphasizes the values ​​of humanity, the third principle which encourages unity amidst diversity, the fourth principle which emphasizes democracy and deliberation, and the fifth principle which focuses on social justice. However, several current challenges threaten the preservation of Pancasila values, such as the decline in religious education, the lack of importance of Pancasila education, the influence of globalization, and deviations in people's behavior, especially among the younger generation. To maintain and strengthen the values ​​of Pancasila, various efforts are needed. One way is to raise awareness through an approach that suits the character of Generation Z, such as utilizing social media as a means of discussion and motivation.